Magnetic Resonance–guided Focused Ultrasound of Uterine Leiomyomas: Review of a 12-month Outcome of 130 Clinical Patients - Gorny, Krzysztof R. (J Vasc Interv Radiol, 2011)
PURPOSE: To assess 12-month outcomes and safety of clinical magnetic resonance (MR)–guided focused ultrasound (US) treatments of uterine leiomyomas. MATERIALS AND METHODS: Between March 2005 and December 2009, 150 women with symptomatic uterine leiomyomas were clinically treated with MR-guided focused US at a single institution; 130 patients completed treatment and agreed to have their data used for research purposes. Patients were followed through retrospective review of medical records and phone interviews conducted at 3-, 6-, and 12-month intervals after treatment to assess additional procedures and symptom relief. Outcome measures and treatment complications were analyzed for possible correlations with the appearance of the tumors on T2-weighted imaging. RESULTS: The cumulative incidence of additional tumor-related treatments 12 months after MR-guided focused US was 7.4% by the Kaplan–Meier method. At 3-, 6-, and 12-month follow-up, 86% (90 of 105), 93% (92 of 99), and 88% (78 of 89) of patients reported relief of symptoms, respectively. No statistically significant correlation between tumor appearance on T2-weighted imaging and 12-month outcome was found. Treatment-related complications were observed in 17 patients (13.1%): 16 patients had minor complications and one had a major complication (deep vein thrombosis). All complications were resolved within the 12-month follow-up period. CONCLUSIONS: MR-guided focused US is a noninvasive treatment option that can be used to effectively and safely treat uterine leiomyomas and delivers significant and lasting symptom relief for at least 12 months. The incidence of additional treatment during this time period is comparable with those in previous reports of uterine artery embolization.